ANALISIS BIBLIOMETRIK: TREN PENELITIAN AUDIT DELAY MENGGUNAKAN SCOPUS DATABASE DALAM DEKADE TERAKHIR [BIBLIOMETRIC ANALYSIS: RESEARCH TRENDS ON AUDIT DELAY USING THE SCOPUS DATABASE IN THE LAST DECADE] - Utami, Nurani; Meidiyustiani, Rinny (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
This study aims to analyze trends and developments in the literature on audit delay using a bibliometric approach with data from the Scopus database and VOSviewer tools. The analysis reveals a significant increase in audit delay-related publications since 2021, with a peak in 2018. The United States is identified as the leading contributor, with the widest research collaboration network, followed by countries such as China, Australia, Indonesia, and Malaysia. The co-citation mapping highlights several thematic clusters focusing on audit efficiency, corporate governance, financial reporting quality, and audit costs. The keyword network visualization indicates that audit delay is closely linked to strategic issues such as firm size, audit opinion, leverage, and digital transformation. Certain topics—such as ERP integration and the role of CEOs—remain underexplored, offering opportunities for future research. Overall, the findings provide a comprehensive overview of the global landscape of audit delay research, identifying key trends and potential research gaps.